Comparing Effects of Low‐ and High‐Volume Moderate‐Intensity Exercise on Sexual Function and Testosterone in Obese Men. (1st May 2013) - Khoo, Joan; Tian, Ho‐Heng; Tan, Benedict; Chew, Kelvin; Ng, Chung‐Sien; Leong, Darren; Teo, Raymond Choon‐Chye; Chen, Richard Yuan‐Tud
Abstract Introduction Obesity and inactivity are associated with erectile dysfunction and hypogonadism. Aim To compare the effects of low volume (LV) and high volume (HV) of moderate‐intensity exercise on sexual function, testosterone, lower urinary tract symptoms (LUTS), endothelial function, and quality of life (QoL) in obese men. Main Outcome Measures Weight, waist circumference (WC), body composition, International Index of Erectile Function 5‐item (IIEF‐5), International Prostate Symptom Scale (IPSS) (for LUTS), and 36‐item Short Form Survey version 2 Instrument (SF‐36) (for QoL) scores, plasma testosterone, sex‐hormone binding globulin, glucose, insulin and lipids, and endothelial function (by Reactive Hyperaemia Index [RHI] using finger plethysmography) were measured at baseline and 24 weeks. Methods Ninety abdominally obese (body mass index > 27.5 kg/m2, WC > 90 cm), sedentary (exercise ∼80 minutes/week) Asian men (mean age 43.6 years, range 30–60) were prescribed a diet to reduce daily intake by ∼400 kcal below calculated requirement and randomized to perform moderate‐intensity exercise of LV (<150 minutes/week) or HV (200–300 minutes/week) (n = 45 each) for 24 weeks. Seventy‐five men (83.3%) completed the study. Results Weekly exercise volume was significantly greater in the HV (236 ± 9 minutes) than the LV (105 ± 9 minutes) group. The HV group had significantly greater increases in IIEF‐5 score (2.6 ± 0.5 points) and testosterone (2.06 ± 0.46 nmol/L) and reductions in weight (−5.9 ± 0.7 kg, −6.2%), WC (−4.9 ± 0.8 cm, −4.9%), and fat mass (−4.7 ± 1.0 kg, −14.5%) than the LV group (−2.9 ± 0.7 kg, −3.0%; −2.7 ± 0.7 cm, −2.5%; −1.1 ± 0.8 kg, −3.2%; 0.79 ± 0.46 nmol/L; and 1.8 ± 0.5 points). Improvements in IPSS and SF‐36 scores, and RHI, were similar. Conclusions Moderate‐intensity HV aerobic exercise > 200 minutes/week produces greater improvements in sexual function, testosterone, weight, WC, and fat mass than smaller exercise volume. Khoo J, Tian H‐H, Tan B, Chew K, Ng C‐S, Leong D, Teo RC‐C, and Chen RY‐T. Comparing effects of low‐ and high‐volume moderate‐intensity exercise on sexual function and testosterone in obese men. J Sex Med **;**:**–**.